Association of Serum Low‐Density Lipoprotein, High‐Density Lipoprotein, and Total Cholesterol With Development of Knee Osteoarthritis. Issue 2 (8th January 2022) - Schwager, Jessica L.; Nevitt, Michael C.; Torner, James; Lewis, Cora E.; Matthan, Nirupa R.; Wang, Na; Sun, Xianbang; Lichtenstein, Alice H.; Felson, David; ,
Abstract : Objective: Studies suggest an association between elevated total serum cholesterol, particularly low‐density lipoprotein (LDL), and osteoarthritis (OA). The present study was undertaken to evaluate the association between total cholesterol, LDL, and high‐density lipoprotein (HDL) and risk of knee OA. Methods: We studied participants from the Multicenter Osteoarthritis study (MOST) cohort at risk of developing knee OA. From baseline through 7 years, repeated knee radiographs and magnetic resonance images (MRIs) were obtained, and knee symptoms were queried. From baseline fasting blood samples, lipids and lipoproteins were analyzed using standard assays. After excluding participants with baseline OA, we defined 2 sets of patients: those developing radiographic OA, and those developing symptomatic OA (knee pain and radiographic OA). Controls did not develop these outcomes. Additionally, we examined worsening of cartilage loss and synovitis on MRI and of knee pain using the Western Ontario and McMaster Universities Osteoarthritis Index scale. We carried out logistic regression adjusting for age, sex, body mass index, education, baseline pain, and depressive symptoms, testing total cholesterol and lipoproteins as continuous measures, and we performed sensitivity analyses examining whether commonly used thresholds for high cholesterol, LDL, or low HDL increased risk. Results: We studied 337 patients with incident symptomatic OA and 283 patients with incident radiographic OA. The mean age at baseline was 62 years (55% women). Neither total cholesterol, LDL, nor HDL showed a significant association with radiographic or symptomatic OA. Additionally, we found no association of these lipid measures with cartilage loss, worsening synovitis, or worsening knee pain. Conclusion: Our data do not support an association between total cholesterol, LDL, or HDL with OA outcomes.